Rhodium (Rh): Metallic complexes applied against cancer (Research, Society and Development, 2025)
This article consists of a review study focused on rhodium (Rh) metal complexes, covering the different possible oxidation states (rhodium(0), rhodium(I), rhodium(II) and rhodium(III)), aiming at a probable application of such coordination compounds in the fight against cancer. Rhodium (Rh) is an element of the platinum (Pt) group and one of the natural candidates for replacing the platinum coordination center in metal complexes that act biologically in a similar way to cisplatin and its analogues and successors. Therefore, the objective of this article is to discuss, through a bibliographic review, the aspects of the coordination chemistry of rhodium (Rh) and its mechanism of action in biological media aiming at its use against different manifestations of cancer, as a possible replacement for the so-called “classical” platinum (Pt) complexes, which are applied against cancer cells of different biological tissues. Finally, future perspectives for the applications of rhodium (Rh) complexes in chemotherapy are presented, as an “anticancer agent”, either alone or as a coadjuvant compound of platinum complexes.